Preserving maritime America : a cultural history of the nation's great maritime museums - Lindgren, James Michael, 1950- (Public history in historical perspective., 2019)
"The United States has long been dependent on the seas, but Americans know little about their maritime history. While Britain and other countries have established national museums to nurture their seagoing traditions, America has left that responsibility to private institutions. In this first-of-its-kind history, James M. Lindgren focuses on a half-dozen of these great museums, ranging from Salem's East India Marine Society, founded in 1799, to San Francisco's Maritime Museum and New York's South Street Seaport Museum, which were established in recent decades. Begun by activists with unique agendas--whether overseas empire, economic redevelopment, or cultural preservation--these museums have displayed the nation's complex interrelationship with the sea. Yet they all faced chronic shortfalls, as policymakers, corporations, and everyday citizens failed to appreciate the oceans' formative environment. Preserving Maritime America shows how these institutions shifted course to remain solvent and relevant and demonstrates how their stories tell of the nation's rise and decline as a commercial maritime power"--